Long-Term Outcomes From Repeated Smoking Cessation Assistance in Routine Primary Care. Issue 7 (September 2018) - Bailey, Steffani R.; Stevens, Victor J.; Fortmann, Stephen P.; Kurtz, Stephen E.; McBurnie, Mary Ann; Priest, Elisa; Puro, Jon; Solberg, Leif I.; Schweitzer, Rebecca; Masica, Andrew L.; Hazlehurst, Brian
Purpose: To test the association between repeated clinical smoking cessation support and long-term cessation. Design: Retrospective, observational cohort study using structured and free-text data from electronic health records. Setting: Six diverse health systems in the United States. Participants: Patients aged ≥18 years who were smokers in 2007 and had ≥1 primary care visit in each of the following 4 years (N = 33 691). Measures: Primary exposure was a composite categorical variable (comprised of documentation of smoking cessation medication, counseling, or referral) classifying the proportions of visits for which patients received any cessation assistance (<25% (reference), 25%-49%, 50%-74%, and ≥75% of visits). The dependent variable was long-term quit (LTQ; yes/no), defined as no indication of being a current smoker for ≥365 days following a visit where nonsmoker or former smoker was indicated. Analysis: Mixed effects logistic regression analysis adjusted for age, sex, race, and comorbidities, with robust standard error estimation to account for within site correlation. Results: Overall, 20% of the cohort achieved LTQ status. Patients with ≥75% of visits with any assistance had almost 3 times the odds of achieving LTQ status compared to those with <25% visits with assistance (odds ratio = 2.84; 95% confidence interval: 1.50-5.37). Results were similar for specific assistance types. Conclusions: These findings provide support for the importance of repeated assistance at primary care visits to increase long-term smoking cessation.